Before Bemberg : Women Filmmakers in Argentina - Losada, Matt (Book collections on Project MUSE., 2020)
"Before Bemberg: Argentine Women Filmmakers calls into question the historiography on Argentine women filmmakers that has centered on María Luisa Bemberg to the exclusion of her predecessors. Its introductory discussion of the abundant initial participation by women in film production in the 1910s is followed by an account of their exclusion from creative roles in the studio cinema, which was only altered by the opportunities opened by a boom in short filmmaking in the 1960s. The book then discusses in depth the six sound features directed by women before 1980, which, despite their trailblazing explorations of the perspectives of female characters, daring denunciations of authoritarianism and censorship, and modernizing formal invention, have been forgotten by Argentine film history. The book recognizes these filmmakers' contributions at a significant moment in which movements to eliminate gender-based oppression and violence in Argentina and elsewhere are surging"--